2018
DOI: 10.3390/ijms19123840
|View full text |Cite
|
Sign up to set email alerts
|

GPCR Modulation in Breast Cancer

Abstract: Breast cancer is the most prevalent cancer found in women living in developed countries. Endocrine therapy is the mainstay of treatment for hormone-responsive breast tumors (about 70% of all breast cancers) and implies the use of selective estrogen receptor modulators and aromatase inhibitors. In contrast, triple-negative breast cancer (TNBC), a highly heterogeneous disease that may account for up to 24% of all newly diagnosed cases, is hormone-independent and characterized by a poor prognosis. As drug resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 262 publications
(316 reference statements)
1
22
0
2
Order By: Relevance
“…Given the appreciation of their role in cancer, the importance of GPCRs for anticancer drug discovery is undisputable, although very few members have been exploited in pursuit of anticancer therapies. In this study, we have confirmed the clinical value of GPSM2.Thus, GPSM2 may be a promising target for new cancer therapy through regulating GPCRs pathway (6,30). Due the value of GPSM2 in predicting disease recurrence, it would be better to add GPMS2 to the NGS panels like Oncotype Dx (31).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Given the appreciation of their role in cancer, the importance of GPCRs for anticancer drug discovery is undisputable, although very few members have been exploited in pursuit of anticancer therapies. In this study, we have confirmed the clinical value of GPSM2.Thus, GPSM2 may be a promising target for new cancer therapy through regulating GPCRs pathway (6,30). Due the value of GPSM2 in predicting disease recurrence, it would be better to add GPMS2 to the NGS panels like Oncotype Dx (31).…”
Section: Discussionsupporting
confidence: 65%
“…G-protein-coupled receptors (GPCRs) regulate numerous essential biological functions (3,4). The abnormal expression of GPCRs is associated with occurrence and development of diverse types of cancer, including breast cancer (5,6). GPSM2 (G protein signaling modulator 2) belongs to a protein family that regulates activation of G proteins (7), which then inhibit GPCR signaling by inhibiting GDP release from Gα subunits (8).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ERα17p acts as an inverse agonist. As such, the motif PLMI could open new avenues for the synthesis of GPER disruptors, which offer hope, as do other GPCR inhibitors, for the treatment of breast cancer [80]. Our work also raises the question as to whether the 295–311 sequence of ERα could correspond to a recruitment platform with the GPER.…”
Section: Discussionmentioning
confidence: 93%
“…OR2T6 belongs to GPCRs, the largest family of cell-surface receptors. GPCRs have been proved to participate in the development and progression of many tumors including breast cancer (36). Consistently, GPCR-based drugs have shown promising efficacy in halting the tumor growth.…”
Section: Discussionmentioning
confidence: 99%